The automated probability-algebraic simulation of the reliability of difficult systems - Sukach, E.I. (PROBLEMS IN PROGRAMMING, 2025)
The approach to research the reliability of difficult systems and the resources of its automation grounded on the method of probability-algebraic simulation is stated, allowing to define the probability characteristics of the reliability of difficult systems under characteristics of reliability of components which make them. The changes occurring to each of components are modeled. Links between the components, defining changes of characteristics of system as a whole are considered.Prombles in programming 2011; 1: 89-98